Potential Oscillation Associated Galvanostatic Deposition of Periodic Al Wires from a Chloroaluminate Ionic Liquid. (5th May 2015) - Su, Chung-Jui; Sun, I-Wen
Abstract : Potential oscillation was observed during the template-free galvanostatic deposition in the 58/42 mol% AlCl3 /trimethylamine hydrochloride ionic liquid, and resulted in the formation of unique periodic (accordion-like) aluminum wires with variable periodicity and diameter controlled by the deposition current density. Factors leading to this phenomenon are postulated.